Modeling and hydrodynamic reconstruction of tidal influenced stromatolites: Yacoraite Formation (Maastrichtian-Danian). Jujuy, Argentina - Villafañe, Patricio (2018)
Fil: Villafañe, Patricio. CONICET, Laboratorio de Investigaciones Microbiológicas en Lagunas Andinas, Instituto Superior de Correlación Geológica; Argentina.